Um novo icnotáxon de tetrápode para a Formação Botucatu, Cretáceo Inferior (Neocomiano) do Brasil: aspectos locomotoriais, preservacionais e paleoecológicos - Buck, Pedro Victor (Universidade Federal de São Carlos, 2016)
Trace fossils (e.g. tracks and trackways), objects of Paleoichnology studys, represent behavioral responses of biota. They are vestiges produced by biological activity of past organisms and can be used for paleobiologicaL, paleoecological and paleoenvironmental reconstructions. The Botucatu Formation (Neocomian) was an immense paleoerg and is know worldwide for its ichnofossiliferous record, comprising traces of vertebrates (dinosaurs and mammal-like tracks) and invertebrates (coleoptera and arachnids). Among vertebrates, are of great importance tracks and trackways from the ichnogenus Brasilichnium Leonardi 1981, endemic of aeolian deposits and assign to mammal-like trackmakers. In the present study is described a new ichnotaxon, Brasilichnium saltatorium isp. nov., with saltatorial progression in phases, distinct and rare in fossil record, attempting to understanding locomotorial aspects and the paleoecology of the geologic unit. The new ichnotaxon show biological variation in behavioural level, and not in preservatonal level, when compared to brasilichnium elusivum, reflecting a great difference in autopodial configuration on trackways. In total, were analyzed 12 trackways, with upward and downard direction relative to the inclined plane of the paleodune. Neoichnological experiment were conducted with Meriones unguiculatus. In the experiment and in fossil trackways, autopodial dimensions are larger in downard direction due to the higher displacement of sediment, and may skew interpretations of the possible trackmaker for change the length/width ratio. Another parameter with the same observation among experiment and fossil trackways is the distance between sets of foot/hand, being greater in the downward direction due to the 4 movement dynamics. Compared to others ichnotaxa presenting the saltatorial locomotion, Brasilichnium saltatorium isp. nov. differs both in morphology of tracks and in the autopodium configuration in trackway, reiterating the new description. Regardless of the direction, the quadruped locomotion appears to be the rule, even when the marks of the hands are not printed, possibly because of the overlap of autopodia and/or production of footprints in the subsurface. Heteropody is most evident in the downward direction, however, it has a higher degree in the upward direction. Based on the study of current desserts, Brasilichnium trackmakers probably were opportunistic omnivores consumers, adopting asymmetrical locomotion to get speed. Near the São Bento Quarry, Araraquara, there must have been ephemeral ponds as a result of pluvial episodes recorded as impact craters in sandstone and the abundant ichnofauna. Such environments could support the biota of the region, enhancing the ecological relationships in these areas and forming locally productive communities.
A new ichnotaxon of tetrapod from Botucatu Formation, Early Cretaceous (Neocomian) from Brazil: locomotorial, preservational, and paleoecological aspects
Keywords: Paleoicnologia; Pegadas fósseis; Mamaliformes; Deserto de dunas; Formação botucatu; CIENCIAS BIOLOGICAS::ECOLOGIA